Adoption rate of land clearing techniques and their effects on some soil fertility parameters of an Alfisol in southwestern Nigeria - Adewole, M. B.; Anyahara, U. C. (African Journal of Agricultural Research, 2023)
INTERNATIONAL African Journal of Agricultural Research:ISSUED 2010, Vol. 5(23), pp. 3310-3315